Faktor Yang Berhubungan dengan Penggunaan Jamban Di Desa Sugai Terap Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Nurussabil, Andi Ahmadiyah; Hilal, T. Samsul; Husaini, Ahmad (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: The use of latrines in the village is still unhealthy because of the habits of the people who use pit latrines in the river. The impact of not using latrines is causing diseases, causing odor , and cause pollution. Objectives: The purpose of this study was to to determine the relationship between education, clean water facilities, the role of health workers, the role of community leaders, knowledge of using latrines Research Metodes: This type of research is descriptive analytic with cross sectional approach. The sampling technique used simple random sampling, the sample was all household in the Sungai Terap 90 people. The analysis used the chi-square test. Results: There is no relationship between education and latrine use, the p-value is 0.957. There is a relationship between clean water facilities and the use of latrines, the p-value is 0.000. There is no relationship between the role of health workers and the use of latrines, the p-value is 0.189. There is a relationship between the role of community leaders and the use of latrines, the p-value is 0.000. There is a relationship between knowledge and latrine use. Conclusion: There is no relationship between education and the role of health workers